Overexpression of amplified in breast cancer 1 (AIB1) gene promotes lung adenocarcinoma aggressiveness in vitro and in vivo by upregulating C-X-C motif chemokine receptor 4 - Liru He; Haixia Deng; Shiliang Liu; Jiewei Chen; Binkui Li; Chenyuan Wang; Xin Wang; Yiguo Jiang; Ningfang Ma; Mengzhong Liu; Dan Xie (Cancer Communications, 2018)
Abstract Background We previously found that overexpression of the gene known as amplified in breast cancer 1 (AIB1) was associated with lymph node metastasis and poor prognosis in patients with lung adenocarcinoma. However, the role of AIB1 in that malignancy remains unknown. The present study aimed to investigate the function of AIB1 in the process of lung adenocarcinoma cell metastasis. Methods A series of in vivo and in vitro assays were performed to elucidate the function of AIB1, while real-time PCR and Western blotting were utilized to identify the potential downstream targets of AIB1 in the process of lung adenocarcinoma metastasis. Rescue experiments and in vitro assays were performed to investigate whether the invasiveness of AIB1-induced lung adenocarcinoma was mediated by C-X-C motif chemokine receptor 4 (CXCR4). Results The ectopic overexpression of AIB1 in lung adenocarcinoma cells substantially enhanced cell migration and invasive abilities in vitro and tumor metastasis in vivo, whereas the depletion of AIB1 expression substantially inhibited lung adenocarcinoma cell migration and invasion. CXCR4 was identified as a potential downstream target of AIB1 in lung adenocarcinoma. The knockdown of AIB1 greatly reduced CXCR4 gene expression at both the transcription and protein levels, whereas the knockdown of CXCR4 in cells with AIB1 ectopic overexpression diminished AIB1-induced migration and invasion in vitro and tumor metastasis in vivo. Furthermore, we found a significant positive association between the expression of AIB1 and CXCR4 in lung adenocarcinoma patients (183 cases), and the co-overexpression of AIB1 and CXCR4 predicted the poorest prognosis. Conclusions These findings suggest that AIB1 promotes the aggressiveness of lung adenocarcinoma in vitro and in vivo by upregulating CXCR4 and that it might be usable as a novel prognostic marker and/or therapeutic target for this disease.